Anaplasma phagocytophilum Activates NF-κB Signaling via Redundant Pathways - Dumler, J. Stephen; Lichay, Marguerite; Chen, Wan-Hsin; Rennoll-Bankert, Kristen E.; Park, Jin-ho (Frontiers in Public Health, 2020)
Anaplasma phagocytophilum subverts neutrophil function permitting intracellular survival, propagation and transmission. Sustained proinflammatory response, recruitment of new host cells for population expansion, and delayed apoptosis are associated with prolonged nuclear presence of NF-κB. We investigated NF-κB signaling and transcriptional activity with A. phagocytophilum infection using inhibitors of NF-κB signaling pathways, and through silencing of signaling pathway genes. How inhibitors or silencing affected A. phagocytophilum growth, inflammatory response (transcription of the κB-enhanced genes CXCL8 and MMP9), and NF-κB signaling pathway gene expression were tested. Among A. phagocytophilum-infected HL-60 cells, nuclear NF-κB p50, p65, and p52 were detected by immunoblots or iTRAQ proteomics. A. phagocytophilum growth was affected most by the IKKαβ inhibitor wedelolactone (reductions of 96 to 99%) as compared with SC-514 that selectively inhibits IKKβ, illustrating a role for the non-canonical pathway. Wedelolactone inhibited transcription of both CXCL8 (p=0.001) and MMP9 (p=0.002) in infected cells. Compared to uninfected THP-1 cells, A. phagocytophilum infection led to >2 fold down regulation of 64 of 92 NF-κB signaling pathway genes, and >2 fold increased expression in only 4. Wedelolactone and SC-514 reversed downregulation in all 64 and 45, respectively, of the genes down-regulated by infection, but decreased expression in 1 gene with SC-514 only. Silencing of 20 NF-κB signal pathway genes increased bacterial growth in 12 (IRAK1, MAP3K1, NFKB1B, MAP3K7, TICAM2, TLR3, TRADD, TRAF3, CHUK, IRAK2, LTBR, and MALT1). Most findings support canonical pathway activation; however, the presence of NFKB2 in infected cell nuclei, selective non-canonical pathway inhibitors that dampening CXCL8 and MMP9 transcription with infection, upregulation of canonical pathway target genes CCL13 and CCL19, enhanced bacterial growth with TRAF3 and LTBR silencing provide evidence for non-canonical pathway signaling. Whether this impacts distinct inflammatory processes that underlie disease, and whether and how A. phagocytophilum subverts NF-κB signaling via these pathways, need to be investigated.